2020
DOI: 10.1016/j.jaip.2020.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Testosterone Is Associated with Decreased Likelihood of Current Asthma Regardless of Sex

Abstract: Background: Asthma prevalence decreases post-puberty in males. Testosterone inhibits airway smooth muscle contraction and attenuates type 2 inflammation.Objective: To investigate the relationship between serum testosterone and current asthma prevalence and lung function in a nationally-representative dataset.Methods: Serum testosterone and self-reported physician-diagnosed current asthma were obtained from 7,584 participants ages 6-80 years from the cross-sectional 2011-2012 National Health and Nutrition Exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 25 publications
4
14
0
Order By: Relevance
“…53 Indeed, increased levels of androgens have been associated with asthma protection in many recent studies. [54][55][56] Moreover, pharmacological and genetic studies support a protective action of androgens. [57][58][59] Supplementation with the androgen dehydroepiandrosterone (DHEA) -which can be metabolized into testosterone, the precursor of DHT, by the dehydrogenase encoded by the HSD3B1 gene -is beneficial in mild to moderate asthma.…”
Section: Discussionmentioning
confidence: 99%
“…53 Indeed, increased levels of androgens have been associated with asthma protection in many recent studies. [54][55][56] Moreover, pharmacological and genetic studies support a protective action of androgens. [57][58][59] Supplementation with the androgen dehydroepiandrosterone (DHEA) -which can be metabolized into testosterone, the precursor of DHT, by the dehydrogenase encoded by the HSD3B1 gene -is beneficial in mild to moderate asthma.…”
Section: Discussionmentioning
confidence: 99%
“…However, the specific role of AR activation in airway physiology is limited. Considering the clinical and epidemiological evidence suggesting intrinsic sex differences in asthma pathophysiology, with men showing lower prevalence and severity of asthma compared with women (61,64,72,73) and the direct correlation of serum androgen levels with reduced asthma symptoms (27,28), warrants for studies on understanding the broad role of androgens in the airways, especially in the context of asthma.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence and severity of asthma remains constant (low compared with females) in men postpuberty, where circulating androgens are at their highest levels (11,25,27). However, this trend is reversed in aged men showing increased severity of asthma symptoms with declined serum testosterone levels, which suggest a potential beneficial role of androgens in asthma (25,27,28). Interestingly, few studies also suggest a beneficial role for androgens in asthmatic women (29).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, decreasing testosterone levels in men older than 45 years was associated with increased asthma prevalence [82]. Participants with asthma aged 6-80 years old from the National Health and Nutrition Examination Survey (n=7584), it was found that in both men and women greater than 12 years old, increased serum testosterone was associated with decreased asthma prevalence in a dose-dependent manner and was associated with increased FEV 1 [83]. In another large cross-sectional study of 256 219 adults aged 40-69 years old in the United Kingdom, increased free testosterone levels were significantly associated with decreased symptoms of asthma, decreased hospitalisations due to asthma in women, and decreased FEV 1 and FVC in men [4].…”
Section: Androgens and Asthmamentioning
confidence: 99%